Brand Analysis Study of International Women University and the Implementation Strategy to the Social Media Communication - Narimawati, Umi; Bunga Gracia, Amanda (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The IWU brand value analysis was carried out using a qualitative method and a quantitative method applied to observe the basic information about the type of social networks they use most, time consumption and their attitude towards the support of celebrities. Three series of questions were asked about the consumption of digital media. 3 different groups were chosen to survey, such as potential students (high school students), parents and alumni, with a total of 30 people. These 3 different groups of respondents have similarities in perceiving that IWU is distinctive and unique and also recognized the international program offered by IWU.